Therapeutic vaccination immunomodulation: forming the basis of all cancer immunotherapy - Brendon J. Coventry (Therapeutic Advances in Vaccines and Immunotherapy, 2019)
Recent immunotherapy advances have convincingly demonstrated complete tumour removal with long-term survival. These impressive clinical responses have rekindled enthusiasm towards immunotherapy and tumour antigen vaccination providing ‘cures’ for melanoma and other cancers. However, many patients still do not benefit; sometimes harmed by severe autoimmune toxicity. Checkpoint inhibitors (anti-CTLA4; anti-PD-1) and interleukin-2 (IL-2) are ‘pure immune drivers’ of pre-existing immune responses and can induce either desirable effector-stimulatory or undesirable inhibitory-regulatory responses. Why some patients respond well, while others do not, is presently unknown, but might be related to the cellular populations being ‘driven’ at the time of dosing, dictating the resulting immune response. Vaccination is in-vivo immunotherapy requiring an active host response. Vaccination for cancer treatment has been skeptically viewed, arising partially from difficulty demonstrating clear, consistent clinical responses. However, this article puts forward accumulating evidence that ‘vaccination’ immunomodulation constitutes the fundamental, central, intrinsic property associated with antigen exposure not only from exogenous antigen (allogeneic or autologous) administration, but also from endogenous release of tumour antigen (autologous) from in-vivo tumour-cell damage and lysis. Many ‘standard’ cancer therapies (chemotherapy, radiotherapy etc.) create waves of tumour-cell damage, lysis and antigen release, thus constituting ‘in-vivo vaccination’ events. In essence, whenever tumour cells are killed, antigen release can provide in-vivo repeated vaccination events. Effective anti-tumour immune responses require antigen release/supply; immune recognition, and immune responsiveness. With better appreciation of endogenous vaccination and immunomodulation, more refined approaches can be engineered with prospect of higher success rates from cancer therapy, including complete responses and better survival rates.